1986
DOI: 10.1007/bf00981142
|View full text |Cite
|
Sign up to set email alerts
|

Influence of physical exercise on the pharmacokinetics of propranolol

Abstract: The pharmacokinetics of propranolol after oral and intravenous administration was studied at rest and on an exercise day in 8 healthy subjects. On the exercise day the subjects performed physical exercise for 7 h, consisting of bicycle ergometer exercise at 50% of maximal work capacity and outdoor walking. Propranolol (80 mg p.o., or 0.2 mg/kg body weight i.v.) was administered 30 min before the start of the exercise. After oral administration the terminal phase halflife, (t1/2 beta) and area under the curve (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…On the other hand, midazolam absorption decreases during moderate exercise, as evidenced by decreased maximal drug concentration (C max ) and absorption rate constant (k a ) and an increased T max in comparison with that at rest (Strömberg et al 1992). In the case of propranolol, bioavailability is reduced during exercise (Arends et al 1986). In most cases, however, no change in absorption has been observed during exercise for quinidine, sodium salicylate, and sulphadimidine (Aslaksen and Aanderud 1980) as well as ephedrine (Strömberg et al 1992) compared with that at rest.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, midazolam absorption decreases during moderate exercise, as evidenced by decreased maximal drug concentration (C max ) and absorption rate constant (k a ) and an increased T max in comparison with that at rest (Strömberg et al 1992). In the case of propranolol, bioavailability is reduced during exercise (Arends et al 1986). In most cases, however, no change in absorption has been observed during exercise for quinidine, sodium salicylate, and sulphadimidine (Aslaksen and Aanderud 1980) as well as ephedrine (Strömberg et al 1992) compared with that at rest.…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies have shown that clearance is a function of hepatic blood flow for many flow-limited drugs, including bromosulfophthalein [Brauer, 19631, hydrocortisone [Paterson and Harrison, 19721, oxyphenbutazone [Whitsett et al, 19711, and lidocaine [Thornson et al, 19711. Experiments studying the effect of exercise on drug elimination of flow-limited drugs have generally agreed with the blood flow dependency hypothesis. As Table 6 illustrates, clearance was decreased during exercise for some flow-limited drugs, such as ampicillin [Cadorniga et al, 19741, caffeine [Kamimori et al, 1986;Hetzler, 1988;Hetzler et al, 19901, ICG [Swartz et al, 1974;Daneshmend et al, 1981;Arends et al, 1986;Mooy et al, 19861, pralidoxime [Swartz and Sidell, 19731, riboflavin [Belko, 19871, sulphadimidine, acetylsulphadimidine, procainainide [Ylitalo and Hinkka, 19851, testosterone [Cadoux-Hudson et al, 19851, and theophylline [Schlaeffer et al, 19841, although the clearance of antipyrine was not significantly changed [Swartz et al, 1974;Theilade et al, 19791. Propranolol, which is flow-limited [Branch et al, 19731, should probably also have a decreased clearance. A study by Arends et al [ 19851 showed a decreased half-life after oral administration of propranolol.…”
Section: Effect Of Exercise On Renal and Hepatic Eliminationmentioning
confidence: 99%
“…The elimination half-life of propranolol, on the other hand, remained unchanged which means that the volume of distribution / clearanceratio of the drug was also unchanged. As has been shown during physical exercise, by decreased indocyanine green clearance (Arens et al 1986), a reduction in hepatic blood flow does not necessarily reduce the clearance of propranolol. On the basis of the theoretical reduction in hepatic blood flow both during exercise and a sauna, certain discrepancies were also observed in our previous studies, when the sauna led to a reduction in the AUC04~ of midazolam, another drug extensively metabolised during first-pass circulation, whereas exercise did not affect the midazolam AUC (Str6mberg et al 1992;Vanakoski et al 1993).…”
Section: Discussionmentioning
confidence: 85%